Perspective of State Sovereignty in Law Enforcement Related to Cyberlaw Jurisdiction - Irawan, Benny; Mulyanti, Dewi; Budiaman, Hendi; Rahman, Yogi Muhammad; Taufiqurrohman, Asari (LAW REFORM, 2025)
Digital development brings both positive and negative impacts. One of the negative consequences of this transformation is the increasing prevalence of criminal activities in the digital realm. This study aims to examine criminal regulatory policies related to cybercrime in Indonesia, particularly those that pose a threat to national sovereignty. The research method employed is normative juridical, using secondary data sources.The findings indicate that criminal law, as a branch of legal science, bears the responsibility of adapting to societal changes—especially in safeguarding citizens, as this is closely linked to state sovereignty. Cybercrime has emerged as a widely discussed issue in both academic and non-academic contexts. These crimes disrupt the security of individuals and threaten national sovereignty, as seen in incidents such as the hijacking of Indonesian citizens’ personal data.The study concludes that more technical regulations are required for addressing cybercrimes committed beyond the territory of the Unitary State of the Republic of Indonesia. One proposed solution is the adoption of a “police-to-police” cooperation framework. This approach is expected to serve as an alternative for the government to respond more effectively to such issues, thereby facilitating the development of laws that are both efficient and effective